Generation of human iPSCs from human prostate cancer-associated fibroblasts IBPi002-A - Kahounová, Zuzana; Slabáková, Eva; Binó, Lucia; Remšík, Ján; Fedr, Radek; Bouchal, Jan; Kurfürstová, Daniela; Vrtěl, Radek; Študent, Vladimír; Jurečková, Lucie; Porokh, Volodymyr; Hampl, Aleš; et al. (Stem cell research, 2018)
A human induced pluripotent stem cell line was generated from cancer-associated fibroblasts of a 68-years old patient with diagnosed prostate adenocarcinoma (PCa). The fibroblast cell line was reprogrammed with Epi5TM Episomal iPSC Reprogramming Kit. Pluripotency of the derived transgene-free iPS cell line was confirmed both in vitro by detecting expression of factors of pluripotency on a single-cell level, and also in vivo using teratoma formation assay. This new iPS cell line may be used for differentiation into different prostate-specific cell types in differentiation studies.
Keywords: Prostatic Neoplasms; lidé; Cancer-Associated Fibroblasts; senioři; fibroblasty asociované s nádorem; indukované pluripotentní kmenové buňky; mužské pohlaví; Male; Induced Pluripotent Stem Cells; Aged; nádory prostaty; fibroblasty; Fibroblasts; Humans